Cartographic works of Russian scientists as a historical source of toponymy - Mominova, Gulnar; Akmaral Sandybayeva, Elmira Alzhanova,; Gulzhan Sugirbayeva, Bekmurat Naimanbayev, (Opción, 2019)
The paper aims to investigate and assess cartographic research works of Russian scientists and determine their historical importance via ethnographic, geographical, and linguistic methods. As a result, toponymy is not only the language of the land or territory, and a book that is not written, but also a historical genealogy that helps to learn the history of a people. The authors concluded that the history of the toponymy of Kazakhstan is an example of a scientific perspective, which requires research due to insufficient knowledge.